Comparative analysis between autogenous and beta phosphate tricalcum associated with hydroxypatite in the maxillary sinus lifting treatment: literature review (Research, Society and Development, 2021)
One of the limitations that make the treatment of implants impossible is the pneumatization of the maxillary sinus. There are different types of graft materials available to the dental surgeon, whether synthetic or natural, which aim to enable vertical bone increase and enable the placement of implants in the region through the elevation of the maxillary sinus. The objective of this work was to identify, through a literature review, histological characteristics, bone behavior and tomographic analyzes in a comparative way between autogenous grafts and Beta tricalcium phosphate associated with hydroxypatite in the treatment of maxillary sinus lifting. this is a literary review that has as database: Scielo, Lilacs and Pubmed through the descriptors: “bone graft”; “biomaterials”; “Maxillary sinus”. Articles published between 2010 and 2021, in the languages: Portuguese, English and Spanish, were included. The following were excluded: monographs, letters to the editor and editorials. Autogenous grafting is still the best option today, even though the biomaterial studied has been successful in the present literature. It is suggested a greater deepening on the use of Beta tricalcium phosphate associated with hydroxypatite in the treatment of maxillary sinus lifting, since there is promising evidence that this can be a strong replacement for autogenous grafting.